Augmentative and Alternative Communication in the Classroom: Teacher Practices and Experiences - Leatherman, Elizabeth M.; Wegner, Jane R. (Language, speech & hearing services in schools, 2022)
Purpose: This study explored the practices and experiences of teachers who teach students using augmentative and alternative communication (AAC), more specifically, speech-generating devices (SGDs). Method: Nine teachers (one general education, eight special education) from four countries participated in semistructured interviews. A generic qualitative approach was taken to inductively code interview transcripts and establish descriptive themes. Results: Three themes emerged from the data. The teaching experience theme captured teachers' feelings, role, collaboration with others, knowledge and learning around AAC, and challenges teaching students who use SGDs. The teaching practices theme included curricula that teachers use, instructional planning, materials and adaptations, instructional strategies, and methods for student evaluation and progress monitoring. Finally, the overarching views and practices theme captured teachers' beliefs and interpretation of the educational system for students using SGDs, as well as teachers' overarching views on communication and approach to AAC implementation. Conclusions: In sharing their perspectives and practices, teachers highlighted a number of constructs that speech-language pathologists could consider when responding to and supporting teacher and student needs. The findings of this study have implications for facilitating collaborative relationships and supporting the use of AAC in schools. Discussion on how educational placement can influence teacher experiences and student outcomes is also integrated into the context of this study.